Determinants of Member Participation at Koperasi Karya Utama Nusantara (Kopkun) Purwokerto - Fega Prasadini; Hary Pudjianto; Herman Sambodo (EKO-REGIONAL, 2019)
This study aimed to examine the effect of member income, length of membership, education level, and distance of residence on member participation of Koperasi Karya Utama Nusantara (Kopkun). Respondents were selected using cluster random sampling. Data were analyzed using multiple regression. This study used a mixed method (quantitative and qualitative approaches). The results indicated that member income, length of membership, and education level had a significant effect on member participation, while the distance of residence did not have an effect on the member participation. The results indicated that in order to increase member participation, Kopkun should improve its services such as providing more items, giving bonuses or benefits to members, providing education about cooperative and involving old and new members in making decisions and policies. Keywords: Cooperative, Mixed Method, Distance of Residence.